Relationship of Catecholamine Metabolism Disorders and Lipid Peroxidation Processes in Women with Metabolic Syndrome - Tashtemirova, I. M.; Kodirova, G. I.; Kodirov, H. N.; Yusuvaliev, M. D. (European Journal of Life Safety and Stability (2660-9630), 2022)
The aim of the given work was study interactions of impairments sympathetic – adrenal systems functional condition and processes of peroxidal oxidation of lipids in woman with metabolic syndrome. 107 women at the age of 25-49 were observation. They were randomized into 3 groups: I (control) – 15 healthy persons, II – 43 patients with arterial hypertension, III – 49 women with arterial hypertension in combination with metabolic syndrome. The results of carried investigations showed that activation of sympathetic adrenal system and processes of peroxidal oxidation of lipids took place in metabolic syndrome. Marked lowering of sympathetic – adrenal system key ferment catecholamins (MAO monoaminooxidaze) desalinization activity and considerable activation of peroxidal oxidation of lipid products which have great significance in revealing the mechanism of metabolic syndrome development were observed in metabolic syndrome. This results in the prolonged toxic influence of catecholamine on myocardium.